Sosialisasi Sosialisasi “Hilangkan Stigma Bahaya Menyelam” Bagi Calon Mahasiswa di Program Studi Ekowisata Bawah Laut - Jurusan Pariwisata - Politeknik Negeri Manado”: Socialization "Eliminating the Stigma of the Dangers of Diving" for Prospective Students in the Underwater Ecotourism Study Program - Tourism Department - Manado State Polytechnic (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
North Sulawesi's maritime potential is well known not only on a national scale but internationally, both in terms of fisheries and tourism. The sea is the main mainstay for increasing regional income. However, specifically the potential for marine tourism, is not supported by comparative human resources between sea area and the availability of educated human resources who have the skills to support marine tourism, especially diving. There is a stigma among the public that diving activities can cause death due to diving errors or even caused by marine animals. The Tourism Department, through the D3 Underwater Ecotourism Study Program, Manado State Polytechnic Tourism Department, feels the need to carry out outreach related to diving activities in the sea. The aim of this student community service activity (PPM-M) is to provide a correct understanding regarding diving activities at sea. Increase in the number of prospective students in the D3 Undersea Ecotourism Study Program. The output of this training is an increase in public understanding regarding the level of diving safety. The location for the socialization is in Tateli Village, which is Campus B, Manado State Polytechnic, Tourism Department, Underwater Ecotourism Study Program.